2008
DOI: 10.1088/1751-8113/41/34/344008
|View full text |Cite
|
Sign up to set email alerts
|

Regularization modeling for large-eddy simulation of homogeneous isotropic decaying turbulence

Abstract: Inviscid regularization modeling of turbulent flow is investigated. Homogeneous, isotropic, decaying turbulence is simulated at a range of filter widths. A coarse-graining of turbulent flow arises from the direct regularization of the convective nonlinearity in the Navier-Stokes equations. The regularization is translated into its corresponding sub-filter model to close the equations for large-eddy simulation (LES). The accuracy with which primary turbulent flow features are captured by this modeling is invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 58 publications
1
42
0
Order By: Relevance
“…An upper bound of the dimension of the global attractor and an analysis of the energy spectrum of the solutions of the 3D version of (2) were established in [10], which suggested that the Leray-α model has great potential to become a good sub-grid scale large-eddy simulation model of turbulence. See also a computational study of this model in [27,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…An upper bound of the dimension of the global attractor and an analysis of the energy spectrum of the solutions of the 3D version of (2) were established in [10], which suggested that the Leray-α model has great potential to become a good sub-grid scale large-eddy simulation model of turbulence. See also a computational study of this model in [27,36,37].…”
Section: Introductionmentioning
confidence: 99%
“…in Geurts and Holm [14,15] or Ilyin et al [21]. The comparison with other LES (or DNS) model predictions are shown and discussed in Chen et al [6], Geurts and Holm [16], Geurts et al [17], Holm and Titi [18], Foias et al [11].…”
Section: Resultsmentioning
confidence: 96%
“…These models are derived from an assumed dynamic principle that is aimed to coarsen the flow description while (Holm et al, 1998). To date, these models were applied to the simplest canonical flow-problems, i.e., homogeneous, isotropic turbulence (Chen et al, 1999;Geurts et al, 2008), and flow in a temporally developing mixing layer (Geurts and Holm, 2006). We reviewed regularized mixing and showed that the results are comparable to and often better than those obtained with the dynamic eddy-viscosity model.…”
Section: Discussionmentioning
confidence: 99%